Continuous aqueous phase reforming of wastewater streams: A catalyst deactivation study. (1st December 2021) - Oliveira, A.S.; Cordero-Lanzac, T.; Baeza, J.A.; Calvo, L.; Rodriguez, J.J.; Gilarranz, M.A.
Graphical abstract: Highlights: Bimetallic PtRe catalyst showed higher activity than monometallic Pt. Re addition to Pt/C catalysts promoted reactions routes favouring deactivation. H2 production increased for modified carbon supports with lower microporosity. Catalyst deactivation was observed due to coke-like matter deposition. Abstract: This paper reports on the catalytic performance and deactivation in aqueous phase reforming of wastewater streams for H2 production. Brewery wastewater was chosen as representative of this type of effluent. The effect of catalyst support textural characteristics was evaluated using an activated carbon and different modified supports obtained by infiltration and carbonization of a phenolic resol resin into activated carbon. The effect of active phase was evaluated using Pt and PtRe catalysts with different metal molar ratio. At short time on stream values, Pt catalysts supported on modified activated carbon showed higher H2 production than those supported on unmodified activated carbon, indicating that a lower microporosity facilitates the transport of reactants to catalytic active sites and release of reaction products. Bimetallic PtRe catalysts showed higher activity than Pt, particularly using a metal molar ratio of 1:1, which yielded the highest H2 production (117.2 μmol min −1 ). Despite the different catalysts tested, early and significant deactivation was observed. The characterization of used catalysts allows postulating the adsorption of organic species and/or coke-like matter deposition on the catalysts surface as main causes of deactivation.